1988
DOI: 10.1177/088626088003001001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Homicide Among Women

Abstract: The population of 136 women arrested in Detroit, Michigan, for homicides committed during 1982 and 1983 is analyzed in the context of their killings. Analyses include demographic and social characteristics of offenders and victims, demographic and social relationships between offenders and victims, circumstances of offense, and arrest disposition. Where feasible, comparisons are made with sex-general populations of homicide offenders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 8 publications
9
57
0
1
Order By: Relevance
“…Further, our findings do conform to earlier research findings that female homicide offenders in America are overrepresented by African Americans (Goetting, 1988;Mann, 1987;Weisheit, 1984). This study found that 67% of the women reported physical abuse as a child, which also conforms to disproportionately high records of victimization (incest, rape, battering) of female offenders found in previous research (Fletcher, Shaver, & Moon, 1993;Belknap & Holsinger, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Further, our findings do conform to earlier research findings that female homicide offenders in America are overrepresented by African Americans (Goetting, 1988;Mann, 1987;Weisheit, 1984). This study found that 67% of the women reported physical abuse as a child, which also conforms to disproportionately high records of victimization (incest, rape, battering) of female offenders found in previous research (Fletcher, Shaver, & Moon, 1993;Belknap & Holsinger, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…No weapon has been chosen relevantly in comparison to others. Location -Homicides perpetrated by women generally occur at home [24], present research confirms previous findings, N=26 committed murder at home.…”
Section: Crime Dynamics and Characteristicssupporting
confidence: 90%
“…Women who kill their abusive partners have been found do so during an argument on a weekend evening, usually with a gun, and while their partners and/or they were under the influence of alcohol (Blount et al, 1988;Ewing, 1987;Goetting, 1988). Of course, all battered women who kill their abusive partners do not fit this profile.…”
Section: Introductionmentioning
confidence: 92%